THE RELATIONSHIP BETWEEN MUSICAL INTELLIGENCE AND THE ENHANCEMENT OF MATHEMATICAL CONNECTION ABILITY USING ETHNOMATHEMATICS AND THE MOZART EFFECT - Dianne Amor Kusuma; Estiyan Dwipriyoko (IKIP Siliwangi and I-MES, 2021)
The background of this study is mathematics learning outcomes of junior high school students in agricultural areas are still low because they are less motivated to learn mathematics, so that is has an impact on their low learning outcomes. This study aims to find the relationship between musical intelligence and the enhancement of mathematical connection ability by applying Ethnomathematics and the Mozart Effect for increasing students’ motivation to learn mathematics. This study used a quasi-experimental non-equivalent control group design in grade 7 students at SMPN Bojongsoang 1, Kabupaten Bandung. The instruments used were the test of mathematical connection ability, musical intelligence questionnaire, and observation sheets. The results showed that: (1) there were differences in mathematical connection ability of students who received Ethnomathematics and the Mozart Effect learning with students who received direct learning; (2) musical intelligence has a positive impact on the enhancement of students' mathematical connection ability; and (3) students have a positive attitude towards learning with application of Ethnomathematics and the Mozart Effect, and more motivated to learn mathematics. The conclusion of this study is that there is a relationship between musical intelligence and the enhancement of mathematical connection ability, and students are more motivated to learn mathematics. Implication of this research for future research and learning practice is that students' mathematical connection ability can be explored and improved in various ways, one of which is by applying Ethnomathematics and the Mozart Effect in mathematics learning, and can be influenced by many things, one of them is musical intelligence. Therefore, in future research, it would be recommended to study the relationship between musical intelligence and the enhancement of other mathematical abilities using Ethnomathematics and the Mozart Effect.